Tumor surveillance for children and adolescents with cancer predisposition syndromes: The psychosocial impact reported by adolescents and caregivers. Issue 8 (31st March 2021) - van Engelen, Kalene; Barrera, Maru; Wasserman, Jonathan D.; Armel, Susan Randall; Chitayat, David; Druker, Harriet; Gallinger, Bailey; Malkin, David; Villani, Anita
Abstract: Purpose: Individuals with cancer predisposition syndromes (CPS) are often followed in cancer screening programs, which aim to detect early stage tumors. While cancer surveillance has the potential to improve patient outcomes, its psychosocial impact is uncharacterized in the pediatric population. We examined the cancer surveillance experience from the perspectives of adolescents and parents of children at risk of developing cancer. Patients and methods: Using grounded theory and thematic analysis qualitative methodology, we conducted semi‐structured interviews with parents and adolescents, separately. Interviews were transcribed verbatim and coded separately to derive overlapping and unique themes. Results: We completed 20 semi‐structured interviews (11 parents and nine adolescents). Positive experiences were related to feelings of reassurance and taking a proactive approach. Both adolescents and parents experienced worry, related to practical aspects of screening, and related to the reminder of cancer risk that manifests with surveillance appointments. This worry was cyclical, associated with appointments, and generally waned over time. Participants felt that the benefits of surveillance outweighed perceived challenges. Open communication with health care providers, and equipping parents/adolescents with vocabulary to discuss their diagnosis and care with others, were felt to be important for mitigating worries associated with cancer risk and surveillance. Conclusion: Parents and adolescents experience worry associated with surveillance for CPS, which may warrant regular psychosocial support, particularly during the first year following CPS diagnosis. Enhancing communication with the health care team and among and beyond immediate family members represents an additional important strategy to mitigate adverse experiences and perceptions.